2014
DOI: 10.1002/cpp.1892
|View full text |Cite
|
Sign up to set email alerts
|

The Individual Therapy Process Questionnaire: Development and Validation of a Revised Measure to Evaluate General Change Mechanisms in Psychotherapy

Abstract: There is a dearth of measures specifically designed to assess empirically validated mechanisms of therapeutic change. To fill in this research gap, the aim of the current study was to develop a measure that covers a large variety of empirically validated mechanisms of change with corresponding versions for the patient and therapist. To develop an instrument that is based on several important change process frameworks, we combined two established change mechanisms instruments: the Scale for the Multiperspective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
1
7

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 51 publications
4
34
1
7
Order By: Relevance
“…Of specific concern is the lack of negative items on short versions of the WAI, including the WAI-S and WAI-SR. As research has not directly examined what is lost in their elimination, the effects of their absence remain unclear. Of note, recently developed measures that expand beyond the construct of the alliance and incorporate more general mechanisms of change do assess more negatively valenced processes (Mander et al, 2013(Mander et al, , 2014. Taken together, the above critiques suggest that both the construct of the working alliance and the way in which it is measured are in need of revision.…”
Section: Problems With Measurement and Methodologymentioning
confidence: 89%
See 1 more Smart Citation
“…Of specific concern is the lack of negative items on short versions of the WAI, including the WAI-S and WAI-SR. As research has not directly examined what is lost in their elimination, the effects of their absence remain unclear. Of note, recently developed measures that expand beyond the construct of the alliance and incorporate more general mechanisms of change do assess more negatively valenced processes (Mander et al, 2013(Mander et al, , 2014. Taken together, the above critiques suggest that both the construct of the working alliance and the way in which it is measured are in need of revision.…”
Section: Problems With Measurement and Methodologymentioning
confidence: 89%
“…The measure consists of seven subscales that reflect different components of psychotherapy process, including general change mechanisms (Gomes-Schwartz, 1978). Two newly developed instruments, the Scale for the Multiperspective Assessment of General Change Mechanisms in Psychotherapy (SACiP; Mander et al, 2013) and the Individual Therapy Process Questionnaire (ITPQ; Mander et al, 2014), integrate existing alliance measures with specific common factors change mechanisms. The SACiP integrated items from the Bernese Post Session Report (BPSR; Fluckiger, Regli, Zwahlen, Hostettler, & Caspar, 2010), a measure of Grawe's (2004) mechanisms of change, and the German WAI-SR (Munder, Wilmers, Leonhart, Linster, & Barth, 2010).…”
Section: Measurementmentioning
confidence: 99%
“…The instrument captures Bordin's () concept of the therapeutic alliance with the three dimensions Bond , Task, and Goal . In several studies, a two factor model with a Bond factor and a Goal & Task factor showed the best psychometric fit (e.g., Falkenström, Hatcher, & Holmqvist, ; Mander et al ., ; Webb et al ., ). The items of the WAI‐SR were rated on a five‐step scale ranging from 1 (does not apply) to 5 (applies fully).…”
Section: Methodsmentioning
confidence: 99%
“…In several studies, a two factor model with a Bond factor and a Goal & Task factor showed the best psychometric fit (e.g., Falkenstr€ om, Hatcher, & Holmqvist, 2015;Mander et al, 2015;Webb et al, 2011). The items of the WAI-SR were rated on a five-step scale ranging from 1 (does not apply) to 5 (applies fully).…”
Section: Methodsmentioning
confidence: 99%
“…WĂ€hrend aktuell Tausende von randomisierten kontrollierten Psychotherapiestudien (RCTs) vorliegen, die in Hunderten von Meta-Analysen zusammengefasst wurden [Hofmann et al, 2012], sind die spezifischen Mechanismen fĂŒr therapeutische VerĂ€nde-rungen kaum bekannt [FlĂŒckiger et al, 2015;Mander et al, 2015b;McMain et al, 2015]. Dies mag unter anderem daran liegen, dass die RCTs typischerweise komplexe Therapiemanuale evaluieren, die aus einer Vielzahl einzelner therapeutischer Bausteine zusammengesetzt sind.…”
Section: Achtsamkeit Und Komponentenstudienunclassified